2005
DOI: 10.1136/jcp.2004.022335
|View full text |Cite
|
Sign up to set email alerts
|

High expression of Mcl-1 in ALK positive and negative anaplastic large cell lymphoma

Abstract: Aim: To gain more insight into the genes involved in the aetiology and pathogenesis of anaplastic large cell lymphoma (ALCL). Methods: Serial analysis of gene expression (SAGE) was undertaken on the CD4+ALK+ (anaplastic lymphoma kinase positive) ALCL derived cell line Karpas299 and as comparison on CD4+ T cells. Quantitative reverse transcription polymerase chain reaction (RT-PCR) and immunohistochemistry were performed on five ALCL derived cell lines and 32 tissue samples to confirm the SAGE data. Results: Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…8 MCL-1 expression could compensate for the lack of immunohistochemically detectable BCL-2 and BCL-XL expression in ALK ϩ ALCL. [9][10][11] Some studies have suggested that the Jak-STAT and PI3K pathways activated in ALK ϩ tumors could be involved in up-regulating MCL-1 but other pathways at the posttranscriptional level, such as microRNAs, might also contribute to its high expression in ALK ϩ ALCL cases (see reviews by Akgul 12 and Michels et al 13 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 MCL-1 expression could compensate for the lack of immunohistochemically detectable BCL-2 and BCL-XL expression in ALK ϩ ALCL. [9][10][11] Some studies have suggested that the Jak-STAT and PI3K pathways activated in ALK ϩ tumors could be involved in up-regulating MCL-1 but other pathways at the posttranscriptional level, such as microRNAs, might also contribute to its high expression in ALK ϩ ALCL cases (see reviews by Akgul 12 and Michels et al 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…8 MCL-1 expression could compensate for the lack of immunohistochemically detectable BCL-2 and BCL-XL expression in ALK ϩ ALCL. [9][10][11] Some studies have suggested that the Jak-STAT and PI3K pathways activated in ALK ϩ tumors could be involved in up-regulating MCL-1 but other pathways at the posttranscriptional level, such as microRNAs, might also contribute to its high expression in ALK ϩ ALCL cases (see reviews by Akgul 12 and Michels et al 13 ).Micro-RNAs (miRNAs) are small noncoding RNAs that regulate target gene expression posttranscriptionally through base pairing within the 3Ј-UTR regions of the target messenger RNAs and inducing their degradation, translational inhibition, or both of the encoded proteins. 14,15 MiRNAs play key regulator roles in fundamental biologic processes including cell differentiation, apoptosis, cell proliferation, organ development, and hematopoiesis (see review by Kluiver et al 16 ).…”
mentioning
confidence: 99%
“…Nevertheless, it is conceivable that ALK-mediated transformation requires a more complex scenario. Comprehensive analyses of the transcriptome of ALK-positive ALCLs are limited and derived from a small number of fresh tissues or ALK-positive cell lines (20)(21)(22)(23). Since ALCL cells often represent a minority within pathological samples and the normal counterpart of ALCL cells is not known, these studies could not be considered paradigmatic.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Mcl-1 is also overexpressed in anaplastic large cell lymphoma, suggesting that this may be the predominant antiapoptotic pathway in this lymphoma. 27 In contrast, Bcl-2 and Bcl-XL are more frequently expressed in anaplastic lymphoma kinase-negative anaplastic large cell lymphoma. 27 A defect in the apoptotic pathway is a hallmark of chronic lymphocytic leukemia (CLL), and differences in chemosensitivity may be attributable to Bcl-2 expression in CLL cells.…”
Section: Clinical Relevance Of Bcl-2 Proteins In Hematolymphoid Maligmentioning
confidence: 99%
“…27 In contrast, Bcl-2 and Bcl-XL are more frequently expressed in anaplastic lymphoma kinase-negative anaplastic large cell lymphoma. 27 A defect in the apoptotic pathway is a hallmark of chronic lymphocytic leukemia (CLL), and differences in chemosensitivity may be attributable to Bcl-2 expression in CLL cells. [28][29][30] Whereas Bcl-2 gene rearrangements are absent in CLL, Bcl-2 protein is overexpressed in CLL cells, 31 indicating that disturbances in the balance between proapoptotic and antiapoptotic proteins may determine the susceptibility of cells to apoptotic signals.…”
Section: Clinical Relevance Of Bcl-2 Proteins In Hematolymphoid Maligmentioning
confidence: 99%